Impact of the Uruguay Round on Sub-Saharan Africa - Harrold, Peter (World Bank, Washington, DC, 2012)
There are six principal reasons why the Uruguay Round (UR) is of interest to Sub-Saharan African (SSA) countries: it will be a boost to the world economy and to demand; It covers agriculture for the first time, especially temperate crops; Non-tariff barriers (NTBs) are critical for Africa, and these are to be abolished; tariff escalation comes down in the round, encouraging industrialization; there are potential losses of preferences for African exporters; and there are new obligations associated with World Trade Organization (WTO) membership. This study, the impact of the Uruguay round on Africa, therefore attempts to measure these different factors to assess their quantitative importance for Africa.